UPPER–STRUCTURE ANALYSIS OF BTS TOWER ON HIGH WIND SPEED AREA - Heru Setiyo Cahyono; Julius Mulyono; Annisa' Carina; Mochammad Hendy Wicaksono; muhammad Koderi Hendrik Waluyo (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2024)
Media transmission (Telcom) tower could be a media transmission building structure that employments a combination of steel outlines as its development fabric. Media transmission towers work as a back for a few media transmission types of gear for transmitting signals that back the cellular communication frameworks that we continuously utilize so remote. Communication. In tower planning, the prevailing powerful stack is wind stack since wind may be a sidelong stack that encompasses a tall affectability to steel development buildings (incorporates a mass that tends to be light). The tallness of the tower that's made depends on the area of the tower itself. The most issue in this inquire about is how to dissect the tower upper–structure in arrange to determine whether it is solid or not to preserve Wind load analysis on BTS (Base Transceiver Station) towers is one of the important aspects in the design of telecommunication tower structures. Wind load can affect the stability and strength of the tower, mainly due to the height of the tower and the nature of the load which tends to change according to the wind speed and the shape of the tower. Study in this research will is about ”Upper–Structure Analysis of Bts Tower on High Wind Speed Area” as a solution to the problems that often occur in the field and until now still often appear structural infeasibility in the selection of construction systems for BTS Tower planning. Results for anlaysis for each joints are : Anchor Bolt Dimensions : 32 mm X 130 cm X 9 units ; Base Plate Dimensions : 50 cm X 50 cm X 32 mm ; Bolts Dimensions for Anchor Joint Type 1 : 16 mm X 40 mm X 5 units ; Bolts Dimensions for Anchor Joint Type 2 : 16 mm X 40 mm X 4 units ; olts Dimensions for Anchor Joint Type 3 : 16 mm X 40 mm X 5 units ; Bolts Dimensions for Anchor Joint Type 4 : 16 mm X 40 mm X 2 units ; Bolts Dimensions for Anchor Joint Type 5 : 16 mm X 40 mm X 2 units ; Bolts Dimensions for Anchor Joint Type 6 : 16 mm X 40 mm X 2 units ; Couple Plate Dimensions : 60 cm ; Bolts Dimension : L 200 X 15 + L 80 x 8.